Preaching and New Worlds
1 online resource (344 pages)
Keywords: This collection of essays examines the polyvalent concept of "New Worlds" in the context of medieval and early modern sermon studies. While the terms "Old World" and "New World" are commonplace in studies of Europe and the Americas, this volume explores how preaching in the Atlantic world and beyond creatively engaged audiences in addressing new cultural and religious perspectives regardless of their geographical location and time period. The identification of the "other" in sermons is already an implicit recognition of a novel world, which could be equally enticing and intimidating. The scholars represented in this volume examine a wide panorama of medieval and early modern efforts as they identify how sermons, which often served as a highly effective media of mass communication, reflect shifting identities, sometimes contested and sometimes embraced, within long-standing traditional constructs. Particular themes include apocalypticism, art and mission, cultural interaction, multilingualism, forms of religious life, and theological innovation.